2023
DOI: 10.1001/jamapediatrics.2023.0115
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Structured Care Coordination for Children With Medical Complexity

Abstract: ImportanceChildren with medical complexity (CMC) have chronic conditions and high health needs and may experience fragmented care.ObjectiveTo compare the effectiveness of a structured complex care program, Complex Care for Kids Ontario (CCKO), with usual care.Design, Setting, and ParticipantsThis randomized clinical trial used a waitlist variation for randomizing patients from 12 complex care clinics in Ontario, Canada, over 2 years. The study was conducted from December 2016 to June 2021. Participants were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…41 However, debate remains about the best way to deliver health care coordination, including health care coordination for people with intellectual disability. 40 , 42 The trial of a care coordination role within the breast screening context could provide important insights into this emerging body of knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…41 However, debate remains about the best way to deliver health care coordination, including health care coordination for people with intellectual disability. 40 , 42 The trial of a care coordination role within the breast screening context could provide important insights into this emerging body of knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Recent national (NICE) guidance 22 recommended that future research should involve examining the effectiveness of ‘dedicated key workers’ and ‘care closer to home’. Results from a recent randomised-controlled trial of care coordination for CMC in Canada 23 have shown that it improves perceptions, but not of other outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these findings emphasize the importance of using an ecological model and a multidisciplinary approach to assess the impact of different system level influences on the outcomes achieved by CC interventions. Despite the proliferation of academic studies highlighting the importance of CC and its recognition in clinical practice, measuring its impact remains challenging (43)(44)(45)(46)(47)(48)(49). Overall, existing CC literature for the pediatric population has used contrasting outcome measures and tools, evaluated interventions in different settings (primary care, tertiary care, emergency department-based interventions, etc.…”
Section: Discussionmentioning
confidence: 99%